Комунікативно-прагматичні характеристики каузального комплексу в англійській та іспанській мовах: зіставний аспект - Леміш, Наталія Іванівна; Lemish, N. I. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті наведено комунікативно-прагматичні характеристики каузального комплексу в англійській та іспанській мовах у зіставному аспекті. Мікроструктури причина–наслідок, підстава–висновок, умова–наслідок, мета–засіб, допуст–наслідок описані з позицій теорії мовленнєвих актів і теорії релевантності. Комунікативно-прагматичні характеристики репрезентовано через комунікативну інтенцію адресанта, стратегії та тактики, що реалізуються в мовленнєвих актах репрезентативів і директивів, оптимальну релевантність висловлення та прагматичну пресупозицію. Особливу увагу приділено варіативності актуального членування каузальних мікроструктур і лінгвальним засобам їх реалізації в мовленнєвих актах. The article deals with communicative and pragmatic characteristics of the causal complex in both English and Spanish languages in comparative aspect. The following microstructures of cause-effect, reason-inference, condition-result, means-purpose, and concession-consequence are considered from the standpoint of Speech Act Theory of J. Searle and Relevance Theory of D. Wilson and D. Sperber. The communicative and pragmatic characteristics under analysis are represented by the speaker’s communicative intention, communication strategies and tactics realized in speech acts of representatives/declaratives and directives. It is also mentioned about the optimal relevance of the statements and pragmatic presupposition. Special attention is paid to the variation of causal micro¬structures actual division – their theme – rheme building, and partly to lingual means of microstructures realization in communicative acts.
Communicative and Pragmatic Characteristics of Causal Complex in English and Spanish Languages: a Contrastive Aspect
Keywords: каузальний комплекс; causal complex; комунікативна інтенція; communicative intention; репрезентативи; representatives